International commodity taxation under monopolistic competition - Andreas Haufler; Michael Pflüger (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2001)
We analyze non-cooperative commodity taxation in a symmetric two- country trade model characterized by monopolistic competition and inter- national firm and capital mobility. In this setting, taxes in one country affect foreign welfare through the relocation of mobile firms and through changes in the rents accruing to capital owners. With consumption-based taxation, these fiscal externalities exactly offset each other and the non-cooperative tax equi- librium is Pareto efficient. With production-based taxation, however, there is an additional externality on the foreign price level which leads non-cooperative tax rates to exceed their Pareto efficient levels.
Keywords: 330; Verbrauchsteuer; Neue Außenhandelstheorie; Ursprungslandprinzip; Steuerwettbewerb; Steuerwirkung; Pareto-Optimum; Theorie; Nichtkooperatives Spiel